If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + 5x + -7 + 5 = 3 + 6x + x Reorder the terms: -11 + -7 + 5 + 5x = 3 + 6x + x Combine like terms: -11 + -7 = -18 -18 + 5 + 5x = 3 + 6x + x Combine like terms: -18 + 5 = -13 -13 + 5x = 3 + 6x + x Combine like terms: 6x + x = 7x -13 + 5x = 3 + 7x Solving -13 + 5x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -13 + 5x + -7x = 3 + 7x + -7x Combine like terms: 5x + -7x = -2x -13 + -2x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -13 + -2x = 3 + 0 -13 + -2x = 3 Add '13' to each side of the equation. -13 + 13 + -2x = 3 + 13 Combine like terms: -13 + 13 = 0 0 + -2x = 3 + 13 -2x = 3 + 13 Combine like terms: 3 + 13 = 16 -2x = 16 Divide each side by '-2'. x = -8 Simplifying x = -8
| 5a-12=18 | | t+45=102 | | -5+2n=7n-5 | | 6q=-9+7q | | (1181*9491)/100 | | iz^2-2z^2=3 | | 1181*9491/100 | | 3/x=9/7 | | 2z/7-7=10 | | (X+15)+(x+10)=180 | | 25j^2+10j+1=0 | | 300=-0.005q^2+2.5q | | 9g=10g+6 | | .7d-15+d=2d-8-.4d | | l-3=9 | | 2(3x+4)=14-3(x-1) | | X^2-13y^2=-1 | | 7a^2x1/9= | | 20+20*0+1= | | 2x-3=-(4x-9) | | -4(9-f)=36 | | .42-.03c=33.3-c | | 2n+2.9=5.5 | | .2(12)+.5x=.1(12+x) | | x^2+9y^2=2 | | d^2+8d-33=0 | | 2x+12=-2x-(8) | | x^3-5x^2-9x+45= | | r=6(b+a) | | 1.02(1.23)(7-x)=8 | | 100/x-10=15 | | =20x^4-100x^3-120x^2 |